Feminino : a mulher, os semblantes, os gozos e as defesas ao (im)possível a suportar - Clara Rodrigues Ottoni (2021)
This paper brings a study on a statement established by Lacan, in the 20th Seminar: More, even more, that “The woman, this can only be written by barring the ‘The’. There is no 'The' woman, an article to designate the universal”. Thus, when stopping the 'The', the psychoanalyst emphasizes that there is no definition for the feminine or a unique way of being a woman, what exists are infinite possibilities of women and that they must be taken one by one in their uniqueness. However, the starting point of this work is the observation that instead of the inexistence of a universal figure that can say that “The” woman brings more freedom for the women subjects to invent their own being; we find that it is a constant to establish an ideal of woman. Therefore, from the paradox of the search for the universal of “The” woman while the feminine refers to the absolutely singular, the central aim of this research is to show and unfold the question: what is (im)possible to endure in the feminine that makes it necessary to defend? Thus, in chapter two, we will behold what is impossible to endure in the feminine. In chapter three, we will approach hysteria as a defense of the feminine, in the forms of the refusal of the body, as well as the enjoyment of deprivation, and the Other woman. Finally, we will portray how the defense of the feminine is manifested in the contemporary from the adoration of digital influencers. As a result, we will see that the Another woman is a substitute for S(The), that is, that hole in the symbolic that does not allow universal writing for the woman because there is an impossibility of this enjoyment to name the woman. Therefore, the impossible to endure is the lack of universal knowledge that can take care of Women and sexual intercourse, considering that this knowledge refers to the order of the singular and, therefore, cannot be shared. Thus, we will see that what Lacan demonstrates is that, as much as there is an insistence on the universal, the enjoyment is of the body and, therefore, cannot be achieved through the Other woman. Faced with this paradox, we consider that the feminine position refers to consent to the duplicity of enjoyments, which implies the abandonment of belief in the whole, the at-least-one that has no flaws and limitations, for an expert with the countenances and with that joy that breaks out. Thus, there is the possibility of experiencing this enjoyment in a life-giving way, that is, compatible with pleasure with life, as it allows the passage from the excluding universal to the otherness of the absolutely singular.